PENAFSIRAN HAKIM TERHADAP ALASAN SALAH SANGKA SEBAGAI PENYEBAB .PEMBATALAN SUATU PERKAWINAN DITINJAU DARI UNDANG-UNDANG NOMOR 1 TAHUN 1974 TENTANG.PERKAWINAN (STUDI KASUS PUTUSAN PENGADILAN AGAMA BANTUL NOMOR 981/Pdt.G/2020/PA.BTL) - Marcelino Valentin; Gunawan Djajaputra (Jurnal Hukum Adigama, 2021)
Marriage cancellation can be done if a marriage does not meet the marriage requirement. Article 27 paragraph (2) of Marriage Law states that the reason for the cancellation of marriage is the existence of misunderstanding regarding the husband or wife. In this writing this law analyzes using legal construction or analogy. In analogy, different but similar, similar, or similar events arranged in law are treated equally. In this writing the result is that homosexual can be the reason for the cancellation of marriage because of a mistaken opinion about the husband. This is done using the method of legal discovery with legal construction argumentum per analogiam on the judge’s decision that grants the cancellation of marriage because the spouse is a bisexual. The legal consequences of the cancellation of marriage result in a relationship between husband and wife, the position of the child, and shared assets. Regarding the relationship between husband and wife, after the existence of a court decision with permanent legal force, marriage is deemed to have never existed, then the child remains a legitimate child and remains the responsibility of both parents. Regarding the joint assets, the agreement between the two parties, the sharing of shared assets must not harm the well-intentioned parties, however, those with good intentions must benefit, even those with bad intentions must bear all losses.